Respostas

2013-01-11T21:56:22-02:00

a) 2x²  -3x + 1 = 0

   delta  = b² -4.a.c

   delta  = (-3)² - 4.2.1

   delta  = 9 - 8

   delta  = 1

   

x1 = -b + raiz(delta)/2a   =     (3 + 1) /4 = 4/4 = 1

x2 = -b - raiz(delta)/2a    =     (3 -  1)/4  =   2/4  =  1/2

 

S ={1 , 1/2}

 

b) -x²  +4x = 0

   delta  = b² -4.a.c

   delta  = (0)² - 4.(-1).4

   delta  = 16

 

x1 = -b + raiz(delta)/2a   =     (0 + 4) /2 = 4/2 = 2

x2 = -b - raiz(delta)/2a    =     (0 -  4)/2  =   -4/2  =  -2

 

S ={-2 , 2}

 

c) 3x² = 0

   delta  = b² -4.a.c

   delta  = (0)² - 0

   delta  = 0

 

x1 = -b + raiz(delta)/2a   =     (0 + 0) /6 = 0

x2 = -b - raiz(delta)/2a    =     (0 -  0)/6 =  0

 

S ={0}

 

d) -x²  + 2 = 0

     -x² = -2

      x²  =  2

      x   =  + raiz(2)

      x  =  -  raiz(2)

 

S ={-raiz(2) , raiz(2)}

 

 

Ta ae mano.. as raizes das funões são as soluções das esquações  ^^

 

12 3 12